Implementasi SOP Produksi Emboss di PT Nikomas Gemilang - Anti Wulan Agustini; Maskanah Maskanah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The manufacturing industry in Indonesia has experienced rapid growth along with the increasing demand from society for various industrial products. This condition encourages manufacturing companies to improve productivity, product quality, and production process efficiency in order to compete in the global market. One of the efforts that companies can undertake is the consistent implementation of Standard Operating Procedures (SOP) at every stage of the production process. This activity aims to determine the implementation of SOP in the emboss production process at PT Nikomas Gemilang and to examine its influence on the work efficiency of operators. The method used in this activity is a qualitative descriptive method with a participatory approach. Data collection was carried out through observation, direct work practice, and documentation during the implementation of the internship program (Kuliah Kerja Praktik/KKP). The results of the activity indicate that the implementation of SOP in the emboss production process has been carried out through several stages, namely the preparation stage, machine operation stage, and production result evaluation stage.